(untitled) - Allen, Dana G. (Philadelphia, 1993)
This new, thoroughly updated edition of a popular formulary includes current drugs and veterinary practices. The practical format is exceptionally concise, portable, and easy to use, and offers readers immediate access to essential information on therapies for dogs, cats, horses, ruminant species, pigs, birds, rodents, rabbits, ferrets, and reptiles. Drugs are logically organized by small, large, and exotic species. Each section begins with a table of dosages and is followed by alphabetically organized entries of commonly prescribed medications. Entries include the generic drug name (and U.S. and Canadian trade names, as appropriate), indications, routes of administration, adverse and common side effects, drug interactions, formulations, and additional drug uses. Dosage conversion tables and formulas are easy to find and use. An easy-scan index speeds readers from drug generic or brand name to complete entries.
Keywords: Veterinary drugs; Handbooks, manuals, etc